BGN May be a Potential Prognostic Biomarker and Associated With Immune Cell Enrichment of Gastric Cancer - Zhang, Shiyu; Yang, Huiying; Xiang, Xuelian; Liu, Li; Huang, Huali; Tang, Guodu (Frontiers in Genetics, 2022)
Background: Biglycan (BGN) plays a role in the occurrence and progression of several malignant tumors, though its role in gastric cancer (GC) remains unclear. The objective of this study was to investigate BGN expression, its role in GC prognosis, and immune infiltration. Material and Methods: Gene expression data and corresponding clinical information were downloaded from TCGA and GTEx, respectively. We compared the expression of BGN in GC and normal tissues and verified the differential expression via Real-Time PCR and immunohistochemistry. BGN-related differentially expressed genes (DEGs) were identified. Additionally, the relationships between BGN gene expression and clinicopathological variables and survival in patients with GC were also investigated through univariate and multivariate Cox regression analyses. Finally, we established a predictive model that could well predict the probability of 1-, 3-, and 5-year survival in GC. Results: We found a significantly higher expression of BGN in GC than that in normal tissues (P<0.001), which was verified by Real-Time PCR (P<0.01) and immunohistochemistry (P<0.001). The 492 identified DEGs were primarily enriched in pathways related to tumor genesis and metastasis, including extracellular matrix (ECM)-receptor interaction, focal adhesion pathway, Wnt signaling, and signaling by VEGF. BGN expression was positively correlated with the enrichment of the NK cells (r = 0.620, P<0.001) and macrophages (r = 0.550, P<0.001), but negatively correlated with the enrichment of Th17 cells (r = 0.250, P<0.001). BGN expression was also significantly correlated with histologic grade (GI&G2 vs. G3, P<0.001), histologic type (Diffuse type vs. Tubular type, P<0.001), histologic stage (stage I vs. stage II and stage I vs. stage III, P<0.001), T stage (T1 vs. T2, T1 vs. T3, and T1 vs. T4, P<0.001) and Helicobacter pylori (HP) infection (yes vs. no, P<0.05) in GC. High BGN expression showed significant association with poor overall survival (OS) in GC patients (HR = 1.53 (1.09–2.14), P = 0.013). The constructed nomogram can well predict the 1-, 3-, and 5-years overall survival probability of GC patients (C-index = 0.728). Conclusion: BGN plays an important role in the occurrence and progression of GC and is a potential biomarker for the diagnosis and treatment of GC.